Towards precision home visiting: results at six months postpartum from a randomized pilot implementation trial to assess the feasibility of a precision approach to Family Spirit - Allison Ingalls; Paul Rebman; Lisa Martin; Elizabeth Kushman; Amanda Leonard; Aimee Cisler; Ingrid Gschwind; Amanda Brayak; Ann Marie Amsler; Emily E. Haroz (BMC, 2022)
Abstract Background Shared implementation challenges at scale in early childhood home visiting have led researchers to explore precision home visiting as a promising service delivery mechanism to better address families' unique needs and build greater program efficiencies. This randomized controlled pilot study aimed to assess the acceptability of a precision approach to one home visiting model, Family Spirit® and explore potential differences between Precision Family Spirit (PFS) and Standard Family Spirit (Standard FS) on participant-home visitor relationship and maternal outcomes. Methods Participants (N = 60) were at least 14 years old, pregnant or within 2 months postpartum, and enrolled in Family Spirit. Four sites in Michigan were randomized 1:1 to deliver PFS (up to 17 core lessons plus up to 13 additional lessons as needed) or Standard FS (home visiting services as usual). Primary (program acceptability, participant satisfaction, home visitor-participant relationship quality, retention, adherence) and secondary (knowledge, quality of life, difficulty with parenting problems, substance use, depression, stress) outcomes at 6 months postpartum are presented. PFS participants also self-reported on quality of life, difficulty with parenting problems, stress, substance use, and concerns with sexual and reproductive health and self and child's nutrition status at each home visit. This informed which lessons they should receive. Results Mothers in both groups reported positive program acceptability, satisfaction, and home visitor-participant relationships at 6 months postpartum. However, open-ended feedback from Standard FS participants indicates that some lesson content may not be applicable to all participants. At 6 months, retention was 82.3% for PFS and 66.7% for Standard FS, and adherence was 30.1% for PFS and 20.6% for Standard FS. Conclusions Preliminary findings indicate that precision home visiting may be acceptable and feasible. A definitive trial is needed to build on this pilot data, assess outcomes for mothers and children participating in a precision approach to home visiting as compared to standard home visiting, and ready this approach for scale. Trial registration ClinicalTrials.gov NCT03975530 (first posted on 05/06/2019).